Dynamic properties of soil-rubber mixtures - Yam, Chau Min (2014)
Recently, many studies were conducted on the use of waste rubber in civil engineering projects. Rubber’s high damping capacity make it a suitable engineering material in soil-rubber mixtures to reduce vibration in seismic design.